2007
DOI: 10.1021/jp0723970
|View full text |Cite
|
Sign up to set email alerts
|

Methylsalicylate:  A Rotational Spectroscopy Study

Abstract: We report the free-jet rotational spectra of methylsalicylate, a molecule with a possible tautomeric and conformational equilibrium. In the ground electronic state, the molecule adopts a form stabilized by an intramolecular hydrogen bond between the phenolic hydrogen and the carbonylic oxygen, and this structure is characterized as the lowest-energy form by quantum chemical calculations. All rotational transitions are split because of the internal rotation of the methyl group, and the value of the barrier for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 22 publications
(26 reference statements)
5
35
0
Order By: Relevance
“…The first dihedral, φ1, shows if the atom close to hydroxyl oxygen is carbonyl oxygen or methoxy oxygen, that is to say, if intramolecular hydrogen bonding is developed through MS1 (φ1 close to 0 o ) or through the MS2 isomers (φ1 close to 180 o ). The results reported in Figure 2 shows that φ1 ~ 10 o (in agreement with results reported by Melandri et al [8]), thus pointing to a clear prevalence of MS1 isomer. Nevertheless, a small population of MS2 isomers (< 5 %) is present along the simulations, this population of MS2 isomers remains almost constant maybe because of the large torsional barrier required for the transformation of MS2 to MS1 [1].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The first dihedral, φ1, shows if the atom close to hydroxyl oxygen is carbonyl oxygen or methoxy oxygen, that is to say, if intramolecular hydrogen bonding is developed through MS1 (φ1 close to 0 o ) or through the MS2 isomers (φ1 close to 180 o ). The results reported in Figure 2 shows that φ1 ~ 10 o (in agreement with results reported by Melandri et al [8]), thus pointing to a clear prevalence of MS1 isomer. Nevertheless, a small population of MS2 isomers (< 5 %) is present along the simulations, this population of MS2 isomers remains almost constant maybe because of the large torsional barrier required for the transformation of MS2 to MS1 [1].…”
Section: Resultssupporting
confidence: 91%
“…Palomar et al [7] reported a vibrational study of intramolecular hydrogen bonding in MS which was discussed together with quantum mechanical calculations, the results showed a fair agreement between experimental and calculated results with bands assigned considering intramolecular hydrogen bonding between the hydroxyl and carbonyl groups. Melandri et al [8] reported a rotational spectroscopy study on MS showing that the ground electronic state of this molecule adopts a form stabilized through the development of intramoleculecular hydrogen bonding between the hydroxyl and carbonyl groups. Massaro et al [9] reported a vibrational analysis of MS isomers showing that the lowest energy isomer is the MS1 form (Scheme 1), in which intramolecular hydrogen bonding between hydroxyl hydrogen and carbonyl oxygen is developed.…”
Section: Introductionmentioning
confidence: 99%
“…Our predictions coincide with experimental observations of ground state IR experiments that assert the existence of only ketoB in liquid MS at normal conditions. 24,25 While there have been computational studies of ES-IPT in small molecules 26 comprising methods such as constant initial state, complete active space self-consistent field, complete active space with second-order perturbation theory (CASPT2), and DFT for several molecules, [27][28][29][30] only one study of MS excited states within ab initio molecular dynamics, AIMD-CASPT2, and 6-31G* basis set 31 exists in the literature. The latter employs highly accurate ab initio methods but calculations were done with a fairly small basis set.…”
Section: Introductionmentioning
confidence: 99%
“…For example, salicylic [17] and benzoic acids [18] were reported to be planar and show P cc values of 0.127 and 0.183 u 2 , respectively. For a planar skeleton of aspirin only the methylic hydrogen atoms would contribute to the planar moment as in methylsalicylate [19] and this would give a value of P cc close to I CH 3 =2 as determined from the internal rotation analysis. The experimental values of the planar moments (about À53 and À58 u 2 , see Table S2 in the Supporting Information) left no doubt that the skeleton of aspirin is nonplanar in both observed conformers.…”
mentioning
confidence: 77%